MENINGKATKAN BAHASA VERBAL MELALUI MEDIA I-CHAT BAGI ANAK TUNARUNGU KELAS IX B DI SMPLB YPPC SAWAHLUNTO (Single Subject Research Kelas IX B di SMPLB YPPC Sawahlunto) - Rahman - Hanifah (Universitas Negeri Padang, 2012)
Against the background of this research by the problems that researchers found in SMPLB YPPC Sawahlunto, a deaf child class IX B minor second semester who have difficulties in verbal language. It is evident, as do interviews and observations were only some teachers who understand the language presented by children with hearing impairment. Researchers also conducted an oral test by saying the ten words (aku, api, baca, buku, curi, kaca, lari, mata, nasi, tahu), but the result of children not just say or express in words that are already available, namely (aku pronounced aghu, api pronounced ebi, baca pronounced maca, buku pronounced bughu, curi pronounced cughi, kaca pronounced ghancah, lari pronounced laghi, mata pronounced mbata, nasi pronounced nasih, tahu pronounced tauh). To overcome this problem researchers are trying to provide an alternative to using I-CHAT media are assumed to be able to help the deaf in the correct pronunciation of orally. This study aims to enhance the deaf child's verbal language class IX B in SMPLB YPPC Sawahlunto. This type of research is the Single Subject Research (SSR) is a study done in different conditions using A B designs. where A is the baseline conditions of the initial condition of the child's ability in verbal language before the given action. While the condition B is a condition in which the intervention condition of children in the intervention provided through the medium of I-CHAT. The size of the target behavior when the child could utter a single word correctly rated the top ten and the one given the value zero. The results of this study shows that verbal language skills of children with hearing impairment in class IX B SMPLB YPPC Sawahlunto media gave rise after the I-CHAT. This terbuktu when the observations made in two sessions: first session provided baseline before intervention (A) is performed five times of observation, and the percentage of verbal language skills in this condition lies in the range of 0%, 0%, 0%, 0% and 0%. Second, the intervention sessions (B) by using the media I-CHAT, the observations were made nine times as many observations, and the percentage of verbal language skills of children with hearing impairment in this condition lies in the range of 50%, 60%, 70%, 70%, 60%, 70 %, 90%, 100%, 100%. Based on these results we can conclude verbal language of deaf children in the class IX B SMPLB YPPC Sawahlunto be increased through the medium of I-CHAT.